The serotonin system : history, neuropharmacology, and pathology - Tricklebank, M. D.; Daly, Eileen (Academic Press, an imprint of Elsevier, 2019)
The Serotonin System: History, Neuropharmacology, and Pathology provides an up-to-date accounting on the physiology and pathophysiology of serotonin and the role it plays in behavioral functions. In addition, the book explores the potential roles of 5-HT1 in neurodevelopmental disorders and summarizes the history of the discovery and development of serotonergic drugs for the treatment of neuropsychiatric disorders. This concise, yet thorough, volume is the perfect introduction to this critical neurotransmitter. It is ideal for students and researchers new to the study of behavior, neuropsychiatry or neuropharmacology, but is also a great resource for established investigators who want a greater perspective on serotonin.